Refeeding Syndrome in Elderly Individuals: Evaluation of a Series of Five Cases - Marcus Vinicius Palmeira Oliveira; David Costa Buarque (Brazilian Society of Geriatrics and Gerontology, 2024)
INTRODUCTION: Undernourishment is a common health problem among elderly individuals, and its prevalence grows among frail patients, which makes nutritional support a priority, especially in acute diseases. However, providing nutritional support to undernourished patients or to those under acute caloric deprivation may lead to electrolyte disturbances associated with neurological, respiratory, and cardiac symptoms, including cardiac arrest. These disturbances occur a few days after receiving nutritional support, and characterize the refeeding syndrome. METHODOLOGY: Five elderly patients hospitalized for clinical reasons and who developed refeeding syndrome during the duration of the stay, were retrospectively evaluated. RESULTS: All patients analyzed were malnourished and frail, of whom four were women. The age group ranged between 82 and 85 years, and food deprivation time ranged between 7 to 15 days. Three patients had severe dementia and were admitted with hypoactive delirium. Hypophosphatemia occurred in 100% of the sample, followed by hypokalemia (60%) and hypomagnesemia (40%). Four patients developed peripheral edema, two developed metabolic ileus and three elderly persons (who had lower phosphorus values) died during the hospital stay. CONCLUSION: All refeeding syndrome patients developed hypophosphatemia, with fatal outcome among those whose phosphorus values were lower. The development of peripheral edema and metabolic ileus was frequent. Owing to the lack of data in literature, new researches on refeeding syndrome are extremely important. Electrolyte evaluation before and after nutritional support in patients at risk, is indispensable to facilitate recognition and treatment of this severe condition.